Preventing Ischial Pressure Ulcers: II. Biomechanics - Hilton M. Kaplan; Lucinda L. Baker; Rahman Davoodi; Nga Ting Wong; Gerald E. Loeb (Applied Bionics and Biomechanics)
Background: Pressure ulcers (PUs) are common and debilitating wounds that arise when immobilized patients cannot shift their weight. Neuromuscular Electrical Stimulation (NMES) has been investigated for Pressure Ulcer Prevention (PUP) for over 20 years. Historically gluteus maximus (GM) has been considered an important actuator in attempting to redistribute seated pressures through NMES.